Next-Generation Sequencing and CRISPR/Cas13 Editing in Viroid Research and Molecular Diagnostics - Hadidi, Ahmed (Viruses, 2019)
Viroid discovery as well as the economic significance of viroids and biological properties are presented. Next-generation sequencing (NGS) technologies combined with informatics have been applied to viroid research and diagnostics for almost a decade. NGS provides highly efficient, rapid, low-cost high-throughput sequencing of viroid genomes and of the 21–24 nt vd-sRNAs generated by the RNA silencing defense of the host. NGS has been utilized in various viroid studies which are presented. The discovery during the last few years that prokaryotes have heritable adaptive immunity mediated through clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated Cas proteins, have led to transformative advances in molecular biology, notably genome engineering and most recently molecular diagnostics. The potential application of the CRISPR-Cas13a system for engineering viroid interference in plants is suggested by targeting specific motifs of three economically important viroids. The CRISPR-Cas13 system has been utilized recently for the accurate detection of human RNA viruses by visual read out in 90 min or less and by paper-based assay. Multitarget RNA tests by this technology have a good potential for application as a rapid and accurate diagnostic assay for known viroids. The CRISPR/Cas system will work only for known viroids in contrast to NGS, but it should be much faster.